Regulatory roles of RNA binding proteins in the Hippo pathway - Shuchang Peng; Chenglin Li; Yanwen He; Lei Xue; Xiaowei Guo (Cell Death Discovery)
Abstract The Hippo pathway represents a highly conserved evolutionary pathway, dysfunction of which has been implicated in various diseases. RNA-binding proteins (RBPs) intricately modulate gene expression through interacting with non-coding RNAs or other proteins. To data, while an array of RBPs have been identified as modulators of the Hippo pathway, there remains a notable absence of a comprehensive review addressing the mechanistic regulations of RBPs in the transduction of Hippo signaling. Herein, this review aims to consolidate recent advances and elucidate the intricate mechanisms underlying RBPs binding to target RNA. It also explores the dynamic interplay between RBPs, non-coding RNAs, TFs, and DNA on chromatin. Additionally, it also outlines future perspectives, including the essential non-canonical functions of RBPs and emerging roles of non-canonical RBPs as transcription factors (TFs) in genes transcription. Overall, this review provides mechanistic insights into the roles of eukaryotic RBP proteins in the regulation of crucial signaling cascades.